KEBIJAKAN NON PENAL DALAM UPAYA PENCEGAHAN DAN PERLINDUNGAN KORBAN TINDAK PIDANA PERDAGANGAN ORANG (TRAFIKING) (Studi Kasus Provinsi Sumatera Utara) - Rina Melati Sitompul; Muhammad Hamdan; Edy Ikhsan; Mahmud Mulyadi (USU LAW JOURNAL, 2014)
ABSTRACT   The title of this thesis is Non Penal Policy in Prevention and Protection Victims of Human Trafficking (A case study in North Sumatera Province). The basis for choosing this title, namely: The increasing number of victims of trafficking, although the law has clear policies seek to prevent and overcome make the Law Number 21 of 2007 on Eradication of Trafficking in Persons as an umbrella act. Based on the results of this study concluded that non penal policy in the national and local regulations, especially North Sumatra, the context of the prevention and protection of victims of trafficking is done by two approaches: 1) prior to the case, namely by strengthening prevention by each institution as a technical holders through the mechanism of inter-organizational system task force institution / SKPDs Government Ordinance No. 9 of 2008 on Procedures Mechanism Integrated Services For Witnesses and / or Victims of Crime of Trafficking in Persons and Presidential Regulation Number 69 of 2008 on the National Task Force on Crime Prevention and Trafficking in Persons (National Policy) and Governor Decree Number 54 of 2010 facilitate coordination and communication patterns between local institutions to the preparation of the work program set out in Governor Decree  No. 53 of 2010 Governor on of North Sumatra Province Action Plan. 2) Victim protection efforts in the aftermath of the case through the physical and psychological recovery (post-traumatic) in the  integrated services unit or DIC (Drop In Center) home safety (P2TP2A). Efforts to strengthen the non penal policy as a form of prevention of Trafficking in Persons in North Sumatra is done by: 1) maximizing the function of the Provincial Task Force through the coordination mechanisms of Article 10-19 Governor Decree No. 54 of 2010 on the Task Force on Crime Prevention and Treatment of Trafficking in Persons in North Sumatera, but not running optimally in a motivating work program on education for each so that non penal policy objectives have not synergize with the purpose and law function.   Key Words: Non Penal Policy, Prevention and Protection, Human Trafficking in North Sumatera.